Serum chemistry profiling and prognostication in systemic mastocytosis: a registry-based study of the ECNM and GREM - Lübke, Johannes; Schmid, Alicia; Christen, Deborah; Oude Elberink, Hanneke N. G.; Span, Lambert F. R.; Niedoszytko, Marek; Gorska, Aleksandra; Lange, Magdalena; Gleixner, Karoline V.; Hadzijusufovic, Emir; Stefan, Alex; Angelova-Fischer, Irena; et al. (Blood advances, 2024)
Certain laboratory abnormalities correlate with subvariants of systemic mastocytosis (SM) and are often prognostically relevant. To assess the diagnostic and prognostic value of individual serum chemistry parameters in SM, 2607 patients enrolled within the European Competence Network on Mastocytosis and 575 patients enrolled within the German Registry on Eosinophils and Mast Cells were analyzed. For screening and diagnosis of SM, tryptase was identified as the most specific serum parameter. For differentiation between indolent and advanced SM (AdvSM), the following serum parameters were most relevant: tryptase, alkaline phosphatase, β2-microglobulin, lactate dehydrogenase (LDH), albumin, vitamin B12, and C-reactive protein (P < .001). With regard to subvariants of AdvSM, an elevated LDH of ≥260 U/L was associated with multilineage expansion (leukocytosis, r = 0.37, P < .001; monocytosis, r = 0.26, P < .001) and the presence of an associated myeloid neoplasm (P < .001), whereas tryptase levels were highest in mast cell leukemia (MCL) vs non-MCL (308μg/L vs 146μg/L, P = .003). Based on multivariable analysis, the hazard-risk weighted assignment of 1 point to LDH (hazard ratio [HR], 2.1; 95% confidence interval [CI], 1.1-4.0; P = .018) and 1.5 points each to β2-microglobulin (HR, 2.7; 95% CI, 1.4-5.4; P = .004) and albumin (HR, 3.3; 95% CI, 1.7-6.5; P = .001) delineated a highly predictive 3-tier risk classification system (0 points, 8.1 years vs 1 point, 2.5 years; ≥1.5 points, 1.7 years; P < .001). Moreover, serum chemistry parameters enabled further stratification of patients classified as having an International Prognostic Scoring System for Mastocytosis-AdvSM1/2 risk score (P = .027). In conclusion, serum chemistry profiling is a crucial tool in the clinical practice supporting diagnosis and prognostication of SM and its subvariants.
Online veröffentlicht: 5. Juni 2024
Gesehen am 27.01.2025